2020
DOI: 10.1002/cam4.3563
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive subgroup analyses of survival outcomes between clear cell renal cell adenocarcinoma and papillary renal cell adenocarcinoma

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 19 publications
1
5
0
Order By: Relevance
“…Conversely, black patients have more favorable survival outcomes than other races, suggesting that the previous conclusion may not be applicable for pRCC. A large population-based study performed by Huang et al showed that non-Hispanic blacks with metastatic pRCC had a higher survival rate than non-Hispanic whites with metastatic pRCC, further proving our conclusion ( 14 ). In addition to age and race, marital status is another important demographic indicator that affects the natural history of many cancers ( 43 , 44 ).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Conversely, black patients have more favorable survival outcomes than other races, suggesting that the previous conclusion may not be applicable for pRCC. A large population-based study performed by Huang et al showed that non-Hispanic blacks with metastatic pRCC had a higher survival rate than non-Hispanic whites with metastatic pRCC, further proving our conclusion ( 14 ). In addition to age and race, marital status is another important demographic indicator that affects the natural history of many cancers ( 43 , 44 ).…”
Section: Discussionsupporting
confidence: 82%
“…Large population-based retrospective cohort studies compared the difference in survival outcomes between pRCC and clear-cell RCC, and the results showed that patients with nonmetastatic pRCC were associated with lower cancer-specific mortality than patients with clear-cell RCC ( 13 ). Nevertheless, patients with pRCC presented a significantly high risk of lymph node metastasis, and the oncologic outcomes of patients with metastatic pRCC were generally more unfavorable than those of patients with metastatic clear-cell RCC ( 14 , 15 ). These findings further suggest that there are different survival outcomes between pRCC and clear-cell RCC.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that age plays a key role in the survival rate of various cancers ( 22 , 23 ). Huang et al found by propensity matching comparison that pRCC had a significantly worse prognosis than ccRCC in patients aged ≤ 45 years ( 24 ). Su et al collected the SEER database of pRCC patients who underwent nephrectomy from 2010 to 2016 for analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Renal cell carcinoma (RCC) is a common urologic malignancy and has increased incidence in recent years 1 . Aside from clear cell renal cell carcinoma (ccRCC), papillary renal cell carcinoma (pRCC) is the most common subtype of RCC and accounts for 10%–15% of all RCC cases 2 . The histology of pRCC is characterized by a papillary fibrous vascular core of tumor cells and is markedly different from that of ccRCC 3 .…”
Section: Introductionmentioning
confidence: 99%
“… 1 Aside from clear cell renal cell carcinoma (ccRCC), papillary renal cell carcinoma (pRCC) is the most common subtype of RCC and accounts for 10%–15% of all RCC cases. 2 The histology of pRCC is characterized by a papillary fibrous vascular core of tumor cells and is markedly different from that of ccRCC. 3 There are two main histological subtypes of pRCC, depending on their characteristics.…”
Section: Introductionmentioning
confidence: 99%